PENGARUH FAKTOR EKONOMI MAKRO, RISIKO INVESTASI DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA (BEI) - Artaya, Made; Anom Purbawangsa, Ida Bagus; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
The significance of the effect of macroeconomic factors, the risk of investmen and financial performance of the stock return is the aim of this study. All companies in Indonesia Stock Exchanges is study population. The analysis technique used is the path analysis, the results of hypothesis testing: (1) interest rates had an insignificant positive effect on investment risk and rupiah exchange rate had a significantly positive effect on investment, (2) the interest rate had an insignificantly positive effect on the Earning Per Share (EPS), the rupiah interest rate had insignificantly negative effect on Eraning Price Ratio (PER), the rupiah exchange rate had an insignificant negative effect on EPS and the rupiah exchange rate had a insignificantly positive effect on the PER, (3) the interest rate had a significant positive effect on stock returns and the rupiah exchange rate did not significantly influence on stock returns, (4) the risk investment had a significantly negative effect on stock returns, (5) EPS had a significantly positive effect on stock returns and PER had a significant positive effect on stock returns.   Keywords: M acroeconomic factors, the risk of investment, financial performance, and stock returns.
Keywords: Macroeconomic factors, the risk of investment, financial performance, and stock returns.